EMOTIONS OF USERS IN FRONT OF EDUCATIONAL VIDEOS: A CASE STUDY FOCUSED ON THE CONSTRUCTION OF GUIDELINES FOR THE PRODUCTION OF MOOCS - Vasconcellos da Luz, Vitória (2023)
In recent decades, the growth of online education practices has been remarkable, aimed at promoting different types of knowledge and also professional training. In this scenario, massive and open online courses (known by the acronym MOOCs) gained greater visibility. In this modality, there is a centrality, in the pedagogical design, of the presence of educational videos. On the other hand, there are studies that characterize the role of emotions as fundamental, capable of accelerating or disturbing the learning process. Therefore, this study aims to analyze the perceptions and emotions of users when watching videos made available in a MOOC, aiming to define guidelines for those who intend to develop videos for MOOCs. The research took place in four stages, the first being a bibliographic review and definition of the method for inferring emotions. The method chosen was the analysis of facial expressions, through the use of the online tool EZ-MMLA ToolKit, which captures the image and defines the emotions, considering the basic emotions and the application of a questionnaire called AEQ (Achievement Emotions Questionnaire) that aims to assess the emotions of achievement experienced during educational tasks, adapted for research. Subsequently, the users' emotions were evaluated when watching the videos. The third step was data analysis and, finally, the definition of guidelines on creating videos for MOOCs. In general terms, it was possible to define that the best accepted video, among those presented, was the one that shows a tutorial and the least accepted was the one that presents synthetic voice narration. Other comments from the participants regarding the analyzed videos emphasize the need for an expressive number of examples with images, less information (short duration videos), removing background music, and, as a positive point, the presence of an avatar and posture who passes the information.